1982
DOI: 10.1901/jaba.1982.15-205
|View full text |Cite
|
Sign up to set email alerts
|

Ritalin vs. Response Cost in the Control of Hyperactive Children: A Within‐subject Comparison

Abstract: A within-subject comparison was made of the effects of methylphenidate (Ritalin) and response cost in reducing the off-task behavior of two boys, 7 and 8 years of age, who had been diagnosed as having an attentional deficit disorder with hyperactivity. Several dosages of Ritalin (5 to 20 mg/day) were evaluated with the results indicating varying effects of the drug for both children. Response cost (with free-time as the reinforcer) was superior to Ritalin in raising levels of on-task behavior and in improving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
1
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(55 citation statements)
references
References 32 publications
(33 reference statements)
3
49
1
2
Order By: Relevance
“…DESCRIPTORS: attention deficit hyperactivity disorder, methylphenidate, behavioral assessment, behavioral pharmacology Methylphenidate (MPH) is often effective for the management of a variety of classroom behaviors associated with attention deficit hyperactivity disorder (ADHD; e.g., Pelham, Bender, Caddell, Booth, & Moorer, 1985;Rapport, Murphy, & Bailey, 1982). However, children are often placed on MPH with little or no objective evaluation of medication effects.…”
Section: Comprehensive School-based Behavioral Assessment Of the Effementioning
confidence: 99%
See 1 more Smart Citation
“…DESCRIPTORS: attention deficit hyperactivity disorder, methylphenidate, behavioral assessment, behavioral pharmacology Methylphenidate (MPH) is often effective for the management of a variety of classroom behaviors associated with attention deficit hyperactivity disorder (ADHD; e.g., Pelham, Bender, Caddell, Booth, & Moorer, 1985;Rapport, Murphy, & Bailey, 1982). However, children are often placed on MPH with little or no objective evaluation of medication effects.…”
Section: Comprehensive School-based Behavioral Assessment Of the Effementioning
confidence: 99%
“…However, the degree of improvement at times varied substantially across dosage and area of functioning. Results suggest that MPH dosage and area of child functioning are critical assessment parameters and that controlled clinical trials are necessary to optimize the effectiveness of treatment with MPH for the individual child.DESCRIPTORS: attention deficit hyperactivity disorder, methylphenidate, behavioral assessment, behavioral pharmacology Methylphenidate (MPH) is often effective for the management of a variety of classroom behaviors associated with attention deficit hyperactivity disorder (ADHD; e.g., Pelham, Bender, Caddell, Booth, & Moorer, 1985;Rapport, Murphy, & Bailey, 1982). However, children are often placed on MPH with little or no objective evaluation of medication effects.…”
mentioning
confidence: 99%
“…By investigating these two aspects of reinforcement separately it is possible to disentangle the processes that may underlie reinforcement sensitivity in ADHD in a within subject design (e.g., Haenlein and Caul 1987;Sagvolden et al 2005). In addition, knowledge regarding the sensitivity of children with ADHD to specific aspects of reinforcement may inform behavioral interventions for ADHD that make use of reinforcement contingencies (DuPaul et al 1992;McGoey and DuPaul 2000;Rapport et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The corollary was that punishment did not work. Accumulated data, however, attest to the continued frequent use of negative feedback in dassroom environments (Strain, Lambert, Kerr, Stagg, & Lenker, 1983;White, 1975), to the efficacy of negative consequences for managing problematic behavior (e.g., Azrin & Powers, 1975;Drabman & Spitalnik, 1973;Iwata & Bailey, 1974;Rapport, Murphy, & Bailey, 1982;Van Houten, Nau, MacKenzieKeating, Sameoto, & Colavecchia, 1982), and to the failure of attempts to conduct dasses using only positive consequences (e.g., Becker, Madsen, Arnold, & Thomas, 1967;Hall et al, 1971;Rosen, O'Leary, Joyce, Conway, & Pfiffner, 1984;Sajwaj, Twardosz, & Burke, 1972). In the most recent attempt, Rosen et al (1984) demonstrated repeatedly that when special education teachers stopped providing negative feedback to students This research was supported in part by a grant from the Middle Country School District No.…”
mentioning
confidence: 99%